PEMODELAN PEMANENAN AIR HUJAN UNTUK MENDUKUNG KONSEP KAMPUS HIJAU DAN PENGURANGAN RISIKO BANJIR - Saragih, Darman Ferianto; Samiran, Samiran; Utami, Citra; Al Qadry, Al Qadry; Nurzanah, Wiwin (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2023)
High rainfall has two conflicting effects. On the one hand, it is beneficial because it has the potential to be used to replace conventional raw water sources. On the other hand, it creates disadvantages caused by flooding. The purpose of this study was to determine the design of a rainwater harvesting system based on the geometric model of the building and the rain regime in such a way that the collected water can replace the use of groundwater so far while at the same time reducing the urban drainage load. The sequential research steps include literature study, determining analysis parameters, designing a Rainwater Harvesting System (RHS) model, creating a spreadsheet-based application (simulation table) for analysis of the RHS's performance, collecting data, analyzing the RHS model using a simulation table, and making conclusions. The RHS simulation designed for the Polmed campus lecture building produces a tank capacity of 45 m3 with a water-saving efficiency of 25% and an efficiency of reducing peak rain runoff of 67.5%. The RHS analysis table resulting from this study can generally be used to design an RHS.